Analysis of Critical Thinking and Communication Skills of High School Students with the Application of Blended Discovery Learning - Maryuningsih*, Yuyun; Gloria, Ria Yulia; Roviati, Evi; Yosriah, Ely (Jurnal Pendidikan Sains Indonesia, 2025)
Critical thinking skills (CTS) and communication skills (CS) in students still need to be improved. This study aims to analyze CTS and CS through the experimental implementation of blended discovery learning (BDL). The research method used is a quasi-experimental design with a pretest-posttest control group design. The study subjects consisted of high school students (SMA) who were divided into experimental and control groups. The experimental group received learning with the BDL model, while the control group used conventional methods. The research instruments were observation sheets for critical thinking and communication skills, as well as CTS tests. The data analysis results showed a significant increase in CTS and communication skills after the implementation of BDL compared to the control group. This increase can be seen from the results of statistical tests that showed a significant difference in pretest and posttest scores in the experimental group. Thus, the implementation of BDL has proven effective in improving CTS and CS, so that it can be an alternative for innovative and interactive learning